Studies on a Water Soluble Polysaccharide from Tinospora cordifolia - Jahfar, M. (Asian Journal of Chemistry, 2010)
Polysaccharide from T. cordifolia was isolated, purified, hydrolyzed and trimethylsilylated; then subjected to GC-MS studies and found (%) arabinose 0.5, rhamnose 0.2, xylose 0.8, mannose 0.2, galactose 0.3 and glucose 98.0.